Pengaruh Intensitas Moral, Sikap Machiavellian dan Self Efficacy terhadap Niat Karyawan Melakukan Whistleblowing di Bidang Keuangan - Meliyana, Friska; Zanaria, Yulita; Kurniawan, Angga (Universitas Muhammadiyah Metro, 2025)
This research aims to analyze the influence of moral instensity, Machiavillian attitudes and Self efficacy on employee intentions to carry out Whistleblowing in the financial ssector PT Agung Jaya Raya Indonesia, Central Lampung. This type of research uses quantitative research with a descriptive apporoach. Data using a questionnaire with a population of 30 respondens from employess who work in the financial sector of PT Agung Jaya Raya Indonesia. The sampling technique used purposive sampling technique using several criteria so that 30 respondents were obtained from working employees. The results of this research show that moral intensity, Machiavillian attitudes and self efficacy influence employee intentions to carry out whistleblowing at PT Agung Jaya Raya Indonesia.